Critical review of floating support structures for offshore wind farm deployment - Leimeister, Mareike; Kolios, Athanasios; Collu, Maurizio (Cranfield University, 2018)
Floating structures enable offshore wind power deployment at numerous deep water sites with promising wind potential where bottom-fixed systems are no longer feasible. However, the large diversity in existing floater concepts slows down the development and maturing processes of floating offshore wind turbines. Thus, in this work, different floating support structures are assessed with respect to their suitability for offshore wind farm deployment. A survey is conducted to examine the capacities of selected floater types, grouped into ten categories, with respect to ten specified criteria focusing on wind farm deployment. By this means, a multi-criteria decision analysis (MCDA) is carried out, using the technique for order preference by similarity to ideal solution (TOPSIS). With the individual scores of the different systems, considering the weighting of each criterion, suitable concepts are identified and potential hybrid designs, combining advantages of different solutions, are suggested.